Investment Performance For Riverside Property Development: The Shore Malacca - Azlina Md. Yassin; Haryati Shafii; Sharifah Meryam Shareh Musa; Bayan Indera Rubaiah (IJEBD (International Journal of Entrepreneurship and Business Development), 2018)
Purpose: This paper aims to determine the challenges in developing riverside property and to identify the investment performance of riverside property development in Malacca. The research was conducted within the case study area namely The Shore Malacca which built next to Malacca River. This riverside development (The Shore Malacca) not only included residential units but also commercial units. It is believed that this type of development is able to bring up the quality of that particular area which then causes the property price to increase. The results were based on the series of interviews conducted with selected respondent which are person directly involved with the development of The Shore Malacca, as well as reviewed several related documents. From the data, there were several challenges identified in developing riverside property in the case study area, and these challenges were then categorised under three category: minor, moderate and major challenges. Moreover, The Shore Malacca has the best investment performance in year 2015 with a highest occupancy rate and the worst investment performance in 2017 with the lowest number of occupied outlet units. This situation happened due to the shrink of economic and the low purchasing power of buyers in real estate market of Malacca. Therefore, this result will help the investor to make decision to investment in Malacca riverfront development and to enhance the economic value of riverfront areas. Design/methodology/approach: This research adopted qualitative research approach along the research process. The Shore Malacca was selected as a case study area. The results were based on the series of interviews conducted with selected respondent which are person directly involved with the development of The Shore Malacca, as well as reviewed several related documents. Findings: The results has identified several challenges while developing The Shore Malacca, and then categorised under three categories: minor, moderate and major challenges. The results also determined the Shore Malacca has the best investment performance in year 2015 with a highest occupancy rate and the worst investment performance in 2017 with the lowest number of occupied outlet units. This situation happened due to the shrink of economic and the low purchasing power of buyers in real estate market of Malacca. Therefore, this result will help the investor to make decision to investment in Malacca riverfront development and to enhance the economic value of riverfront areas. Research limitations/implications: in this research, investment performance is seen from the business performance (operational) in the Shore Malacca. Since some information is considered confidential especially in terms of profit, the results was not viewed holistically, but were based on respondent justifications. Practical implications: Hopefully, this result will help the investor to make decision to investment in Malacca riverfront development and to enhance the economic value of riverfront areas. Originality/value: This research combines the study of real estate and investment performance. Moreover, this research had employed series of interviews with respective stakeholders that directly involved in the riverfront projects. Paper type: Research paper